Health Risk Due to Carbamate Exposure in Communities Around Paddy Field Areas - Maksuk - Maksuk; Sherli - Shobur; Suzanna - Suzanna (Universitas Airlangga, 2021)
Introduction: Carbamate is one of the most widely used pesticides in paddy field areas, which causes environmental pollution and human health problems. Therefore, this study aims to analyze the health risks of carbamate exposure in communities around paddy fields areas. Methods: This was an observational analysis study conducted using the health risk assessment approach. There were 20 samples of waterway streams from 10 sites observed in the morning (at high tide) and evening (at low tide) taken using a grab sampling method. The parameters of the waterway streams river, such as pH and temperature, were measured on-site using a pH meter and portable thermometer, while the carbamate concentration was analysed in the laboratory using High-Performance Liquid Chromatography (HPLC). Results and Discussion: The active ingredients of carbamate pesticides that observed as follows: aldicarb (0 – 0.05 mg/l), carbaryl (0 – 0.01 mg/l), carbofuran (0-0.005 mg/l), and propoxur (0-0.001 mg/l). While the pH (6.4 – 7.5) and temperature (22.1 – 32.4oC). The potential exposure of Aldicarb in grown-up and kids were 0.042 and 0.077 mg/kg bodyweight-day, respectively. Furthermore, the potential exposure of carbofuran in Grown-ups and kids were 0.004 and 0.01 mg/kg bodyweight-day, respectively. Only the carbofuran exposure in kids has a rate of RQ > 1, which is unsafe or can cause non-carcinogenic effects in the next 30 years. Conclusion: Although the carbamate concentrations in waterway streams around paddy field areas were below the quality standard, it is not safe. Therefore, it is necessary to carry out risk management and communication with local policymakers.